Effects of atherogenic diet supplemented with fermentable carbohydrates on metabolic responses and plaque formation in coronary arteries using a Saddleback pig model. - Lisa Wahl; Melina Raschke; Johannes Wittmann; Armin Regler; Steffen Heelemann; Corinna Brandsch; Gabriele I Stangl; Ingrid Vervuert (PLoS ONE, 2022)
Fermentable carbohydrates are gaining interest in the field of human nutrition because of their benefits in obesity-related comorbidities. The aim of this study was to investigate the influence of fermentable carbohydrates, such as pectin and inulin, in an atherogenic diet on metabolic responses and plaque formation in coronary arteries using a Saddleback pig model. Forty-eight healthy pigs aged five months were divided into four feeding groups (n = 10) and one baseline group (n = 8). Three feeding groups received an atherogenic diet (38% crisps, 10% palm fat, and 2% sugar with or without supplementation of 5% pectin or inulin), and one group received a conventional diet over 15 weeks. Feed intake, weight gain, body condition score, and back fat thickness were monitored regularly. Blood and fecal samples were collected monthly to assess the metabolites associated with high cardiovascular risk and fat content, respectively. At the end of 15 weeks, the coronary arteries of the pigs were analyzed for atherosclerotic plaque formation. Independent of supplementation, significant changes were observed in lipid metabolism, such as an increase in triglycerides, bile acids, and cholesterol in serum, in all groups fed atherogenic diets in comparison to the conventional group. Serum metabolome analysis showed differentiation of the feeding groups by diet (atherogenic versus conventional diet) but not by supplementation with pectin or inulin. Cardiovascular lesions were found in all feeding groups and in the baseline group. Supplementation of pectin or inulin in the atherogenic diet had no significant impact on cardiovascular lesion size. Saddleback pigs can develop naturally occurring plaques in coronary arteries. Therefore, this pig model offers potential for further research on the effects of dietary intervention on obesity-related comorbidities, such as cardiovascular lesions, in humans.